Impact of Economic Liberalization Policy on Economic Activity in Sudan during the Period (1992- 2018) - Nour, Ali Elhassan Mohammed; Seed, Mohsin Mahir; Gifoon, Abdelazeez Mozamil (Journal of Economic, Administrative and Legal Sciences, 2022)
This study examined the impact of economic liberalization policy on economic activity in Sudan during the period (1992- 2014). The study aimed to recognize the macroeconomic indicators after the application of economic liberalization policy, also to show the effect of the economic liberalization policy on economic activity in Sudan. The study assumed there are a positive relationship between (exports, imports, and GDP) and negative relation between (money supply) and openness as a dependent variable. Also there is a positive relationship between (GDP) as dependent variable and) foreign direct investment FDI) as explanatory variables and a negative relationship with exchange rate. Foreign direct investment related negatively to exchange rate. The study used the analytical and descriptive method, by using ordinary least squares method (OLS), through the program (Eviews). The more important results of the study showed that (exports, imports, and GDP) had a positive impact on openness, also it’s a proved that the currency devaluation is effected the economic activity in Sudan negatively. Also the results proof the significant hypotheses of the study (the positive effect of FDI on GDP and negative effect of exchange rate). The study recommended that there must be an increase on investment projects which leads to increases in goods and services, all that will decreases the inflation rate, and finally encourage foreign direct investment.